"\\mathcal{L} (sin(5t+6) ) = \\int_0^{\\infty} e^{-st} sin(5t+6) dt"
Let, "I = \\int e^{-st} sin(5t+6) dt"
"= [ \\frac{-1}{s} e^{-st} sin(5t+6)] - \\int\\frac{-5}{s} e^{-st} cos(5t+6)dt"
"= [ \\frac{-1}{s} e^{-st} sin(5t+6)] - [\\frac{-5}{s^2} e^{-st} cos(5t+6) + \\int \\frac{25}{s^2} e^{-st} sin(5t+6)dt]"
"I = [ \\frac{-1}{s} e^{-st} sin(5t+6)] - [\\frac{-5}{s^2} e^{-st} cos(5t+6)] - \\frac{25}{s^2}I"
then solving it,
we get,
"I = \\frac{e^{-st}}{s^2 + 25}[ -ssin(5t+6) - 5cos(5t+6) ]"
Now, putting the limits,
"\\mathcal{L} (sin(5t+6) ) = \\int_0^{\\infty} e^{-st} sin(5t+6) dt = \\frac{1}{s^2 + 25} [ ssin(6) + 5cos(6)]"
Comments
Leave a comment